The Effects of Currency Substitutionon the Response of the Current Account to Supply Shocks. (IMF Working Papers; Working Paper ;, 1988)
Standard real models predict that a permanent increase in oil prices would result in a current account surplus. This is due to the fact that investment falls while saving remains unchanged. This paper shows that if currency substitution is introduced into the analysis, the same shock could cause a current account deficit. Furthermore, the higher the dependence of the economy on oil, the larger would be the deficit. The presence of foreign money makes it optimal for the public to decrease saving following the terms of trade deterioration. The fall in saving could be larger than the decline in investment.